Investigation of a Reduction in Tylosin on the Prevalence of Liver Abscesses and Antimicrobial Resistance in Enterococci in Feedlot Cattle - Davedow, Taylor; Narvaez-Bravo, Claudia; Zaheer, Rahat; Sanderson, Haley; Rodas-Gonzalez, Argenis; Klima, Cassidy; Booker, Calvin W.; Hannon, Sherry J.; Bras, Ana L.; Gow, Sheryl; McAllister, Tim (Frontiers in Veterinary Science, 2020)
Recent concerns over linkages between antimicrobial resistance in human pathogens and antimicrobial use in livestock have prompted researchers to investigate management strategies that reduce the current reliance on in-feed tylosin, to control liver abscesses in feedlot cattle. A total of 7576 crossbred yearlings were allocated to the study (~ 253 animals/pen, 10 replicate pens per treatment) and individually randomized to one of three treatments. Tylosin phosphate (11 ppm) was included in-feed 1) for the first 125 days on feed (DOF) (FIRST-78%), 2) for DOF 41 to 161 (LAST-75%), or 3) for the entire feeding period (CON; day 0 to 161). Fecal composites were collected from the pen floor on days 0, 81, and 160 of the finishing period. Serial dilutions were spread plated for enumeration of enterococci on Bile Esculin Azide (BEA) agar and BEA amended with 8 µg/ml erythromycin. Results indicated that although the proportion of EryR enterococci increased with DOF (P < 0.01), neither treatment (P = 0.34) or treatment x DOF (P = 0.37) affected antimicrobial resistance. Of the 538 isolates, 97% were enterococci, with mixed species isolated early in the feeding period and only Enterococcus hirae isolated at the end. Isolates were most frequently resistant to tylosin (86%), erythromycin (84%) and doxycycline (31%). Macrolide and tetracycline resistant isolates harbored erm(B), msrC and tet(L), tet(M), tet(O) genes, respectively. Overall, the proportion of EryR enterococci increased (P < 0.05) in all three treatments over the feeding period. Cattle administered tylosin for a shorter duration had more severe (P < 0.05) liver abscesses compared to the control, but there was no difference (P > 0.05) in total liver abscesses, growth performance, carcass traits, morbidity or mortality. These results support the potential to reduce the duration and therefore quantity of tylosin administration in feedlot cattle without impacting animal productivity.